PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT ASIDOSIS TUBULUS RENALIS MENGGUNAKAN METODE CERTAINTY FACTOR DENGAN PENULUSURAN FORWARD CHAINING - Rahmi Ras Fanny; Nelly Astuti Hasibuan; Efori Buulolo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
Renal tubular acidosis and commonly referred to as kidney disease, especially in the renal tubules, according to some scientific medical fields of renal tubular acidosis are quite rare, with clinical manifestations that are not specific so that the diagnosis is often delayed. In normal circumstances, the kidneys absorb the acid of the metabolic waste from the blood and throw it into the urine. The cause of renal tubular acidosis disease is due to hereditary factors or may result from medications. Forward Chaining is a search method or tracking technique that begins with existing information merging rules to produce a conclusion or goal. This advanced tracking is great if it works with problems that start with the initial information recording and the final completion, as the whole process will be done in sequential order.